High‐Surface‐Area Porous Platinum Electrodes for Enhanced Charge Transfer. Issue 14 (2nd June 2014) - Hu, Yelin; Yella, Aswani; Guldin, Stefan; Schreier, Marcel; Stellacci, Francesco; Grätzel, Michael; Stefik, Morgan
<x xml:space="preserve">Abstract</x> Cobalt‐based electrolytes are highly tunable and have pushed the limits of dye‐sensitized solar cells, enabling higher open‐circuit voltages and new record efficiencies. However, the performance of these electrolytes and a range of other electrolytes suffer from slow electron transfer at platinum counter electrodes. High surface area platinum would enhance catalysis, but pure platinum structures are too expensive in practice. Here, a material‐efficient host‐guest architecture is developed that uses an ultrathin layer of platinum deposited upon an electrically conductive scaffold, niobium‐doped tin oxide (NTO). This nanostructured composite enhances the counter electrode performance of dye‐sensitized solar cells (DSCs) using a Co(II/III)BPY3 electrolyte with an increased fill factor and power conversion efficiency (11.26%), compared to analogous flat films. The modular strategy is elaborated by integrating a light scattering layer onto the counter electrode to reflect unabsorbed light back to the photoanode to improve the short‐circuit current density and power conversion efficiency.